MORPHOLOGICAL ANALYSIS AND ACCUMULATION OF NUTRIENTS IN Peltophorum dubium (Spreng.) Taub. SEEDLINGS PRODUCED IN ORGANIC SUBSTRATES WITH DIFFERENT PROPORTIONS - Melo Nunes Astolfi, Angelica Christina; da Silva Mota, Lucas Junior; Pontes, Montcharles da Silva; Clemente, Leyzinara Zenteno; Santiago, Etenaldo Felipe; de Carvalho, Laércio Alves; Motta, Ivo de Sá (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
Environmental conservation and regeneration actions must consider plant species that add value by restoring structural and functional aspects of the ecosystem. The forest species, Peltophorum dubium, has several characteristics that make its use viable in projects of restoration of degraded areas, making it necessary to study the species’ responses to different cultivation environments. Thus, 500 seeds were selected and sown in vermicompost substrates prepared with different proportions of cattle rumen content (CR) and sugarcane bagasse (SB) (V1 - 60% CR x 40% SB / V2 - 50% CR x 50 % SB / V3 - 40% CR x 60% SB / V4 - 70% CR x 30% SB) and in an commercial substrate (Plantmax®). At 79 days after sowing, 20 seedlings per treatment were removed; they were weighed and measured, resulting in growth, dry matter, and vigor data. The vermicompost substrates were sent to the chemical analysis laboratory to determine their chemical composition. The data were submitted to normality analysis. Analysis of variance was performed for normal data and the Kruskal Wallis test for data that did not show normality. The means or medians were compared using the Tukey test at a 5% probability level. Based on the results related to the growth and vigor of P. dubium seedlings, it is possible to state that the productive potential of the species was higher in the vermicompost substrates.